Energy carriers production from organic waste of agriculture - Komar, Artem; Комар, Артем Станіславович; Комар, Артем Станиславович (My University, 2021)
The rapid exhaustion and rise in price of primary energy carriers, as well as a significant deterioration in the environmental situation on the planet, contributed to the production of alternative energy resources and effective methods for the disposal of organic waste. In agriculture, organic waste can be divided into plant waste and animal husbandry.
Keywords: energy carriers; samethods for the dispol; organic waste